(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
This article represents analysis of the technical capabilities of the specialized forest milling machine PT-400 with multi-purpose forestry tiller FAE-300/S for mulching, stump grinding and for deep soil preparation for establishment of intensive forest poplar cultures. The operating productivity, the optimal ways of movement, production capacity and some basic quality indicators of the machine have been determined under specific working conditions. The survey has been conducted on poplar sites and slashes along the Danube river valley.